Support Methodologies for African American Women With Lupus – Comparing Three Methods’ Effects on Patient Activation and Coping - White, Ashley; Faith, Trevor D.; Ba, Aissatou; Loftley, Aundrea; Ramakrishnan, Viswanathan; Johnson, Hetlena; Rose, Jillian; Dismuke-Greer, Clara L.; Oates, Jim C.; Egede, Leonard E.; Williams, Edith M. (Frontiers in Psychology, 2021)
Background: Systemic Lupus Erythematosus (SLE) is a chronic inflammatory disease in which the immune system attacks healthy tissues. While pharmaceutical therapies are an important part of disease management, behavioral interventions have been implemented to increase patients’ disease self-management skills, provide social support, and encourage patients to take a more active role in their care. Methods: Three interventions are considered in this study; peer-to-peer methodology, patient support group, and a patient navigator program were implemented among largely African American women with SLE at the Medical University of South Carolina (MUSC). Outcomes of interest were Patient Activation and Lupus Self-Efficacy (coping). We used a Least Squares Means model to analyze change in total patient activation and coping independently in each cohort. We adjusted for demographic variables of age, education, income, employment, and insurance. Results: In both unadjusted and adjusted models for patient activation, there were no statistically significant differences among the three intervention methodologies when comparing changes from baseline to post intervention. Within the unadjusted model, differences in total coping from baseline to post intervention with the Patient Navigator and differences in scores comparing the Patient Navigator with the Support Group were statistically significant. However, upon adjustment for demographic characteristics, only the difference in total coping from baseline to post intervention for the Patient Navigator program remained statistically significant. Conclusion: Tailored interventions are a critical pathway toward improving disease self-management among SLE patients. Interventions should consider including patient navigation because this method was shown to be superior in improving self-efficacy (coping scores).